(untitled) (Feni University Journal, 2026)
The listed firm is directed to abide by the standards set forth by the Bangladesh Securities and Exchange Commission in 2018 to guarantee appropriate corporate governance. This research investigates the correlation between Bank Characteristics in Bangladesh and Corporate Governance Disclosure. Six hypotheses are tested, focusing on dependent variables like Corporate Governance Disclosure (major components of corporate governance activities) and six independent variables (Bank Characteristics). The annual report from July 2020 to July 2021 for 32 banks enlisted under the Chittagong Stock Exchange (CSE) was used to conduct this study. The author processes the data with the help of Excel and SPSS and analyzes it through correlation and regression analysis. After conducting a comprehensive study and interpreting the statistical results to test the pertinent hypotheses, it has been concluded that only three variables (bank characteristics), i.e., age of listing with CSE, affiliation with a multinational bank, and bank board size, have a favorable effect on Corporate Governance disclosure. Other variables, such as bank net profit, bank size, and percentage of independent directors, have a significant positive impact on Corporate Governance disclosure according to correlation and regression analysis, respectively. This study generates value for the institutions involved, as well as for other relevant stakeholders. This study may impact the decisions made by creditors and investors. FENI UNIVERSITY JOURNAL, 2024, 3(1), ISSN [2518-3869], PP. (113-130)